Fostering critical thinking and self-efficacy in mathematics students: Exploring the impact of contextual learning and problem-based learning as well as direct instruction - Dwi Yulianto; Moh Rizal Umami; Randa Sarah Mony (Universitas Sarjanawiyata Tamansiswa, 2024)
This research addresses the low critical mathematical thinking abilities of students when facing mathematical problem-solving challenges. The study aims to evaluate the impact of implementing various teaching approaches, including Contextual Teaching and Learning (CTL), Problem-Based Learning (PBL), and Direct Instruction (DI) models, on students' critical mathematical thinking abilities. Participants included 276 eighth-grade students from SMP La Tansa Mashiro 1, 2, and 3 in Lebak Banten during the academic year 2022/2023, divided into three classes. Samples were selected using simple random sampling, resulting in 94 students for CTL, 92 students for PBL, and 90 students for DI instructional models. Data collection involved self-efficacy questionnaires and critical mathematical thinking ability tests, analyzed using a two-way ANOVA. The findings suggest that implementing CTL and PBL models positively influences students' critical mathematical thinking abilities. Additionally, students' self-efficacy levels contribute significantly to their critical mathematical thinking abilities. Furthermore, a significant interaction was observed between the implementation of CTL, PBL, and DI models and students' efficacy levels, collectively influencing students' critical mathematical thinking abilities. These results emphasize the importance of employing active approaches, such as contextual, problem-based, and direct instructional methods, while also enhancing students' self-confidence to improve their critical mathematical thinking abilities. It is hoped that implementing these recommendations will enhance the effectiveness of mathematics learning and foster the development of students' critical thinking skills.